Empowering Students: How Teachers’ Autonomy Support Shapes Self-Efficacy for Self-Regulated Learning - Jahju Hartanti; Lucky Nindi Riandika Marfu’i; Ana Musdalifah; Erasmos Charamba (Jurnal Ilmu Pendidikan, 2025)
Education autonomous support of teaching can promote students learning. This study collected 409 teachers survey questionnaires and applied structural equation model to measure teacher autonomy support, student self-efficacy, and student self-regulated learning. This study adopted self-determination theory (SDT), systematically explored the relationship between teachers’ autonomy support, student self-efficacy and student self-regulated learning and examined the mediating effects of students’ self-efficacy. This study found that teacher autonomy support had a significant effect on student self-regulated learning, and was mediated by self-efficacy. Teacher-directed support had a significant effect on student self-efficacy. Therefore, this study gave a fresh perspective to improve learning engagement, that is to say, teachers were encourage to improve students’ autonomy in practical teaching on the basis of giving students autonomy support.